Communication Skill Training of Bunda PAUD at Pakal Surabaya to meet the Competency as Professional Educator - Dewi Khrisna Sawitri; Wiwik Handayani; Ika Korika Swasti; Devinda Anggitasari; Fatimah Kalitdyah; Nur Aini Rahmaniah (ABDIMAS: Jurnal Pengabdian Masyarakat, 2022)
This service is intended to improve the competence of educators in terms of communication soft skills of PAUD educators in interacting with their students. The training participants are PAUD educators from Pakal sub-district who will practice developing their communication skills, especially those related to non-verbal communication. This training is done to refresh and improve their non-verbal communication so that they are ready to teach offline. in the offline teaching process, they will interact directly with their students which they have been doing during online learning during the covid period. The non-verbal communication training provided also focuses on the practice of communicating with the role play between PAUD Mothers and students who act as early childhood students. This training showed significant results in the form of increased understanding in which Bunda PAUD can perform the appropriatenon verbal communication skills. In addition, success in this training is also shown from the practice of role-playing implementing efficient non-verbal communication with the emergence of haptics, oculesics, and proxemics.